Altered Iron Metabolism and Impact in Cancer Biology, Metastasis, and Immunology - Brown, Rikki A. M.; Richardson, Kirsty L.; Kabir, Tasnuva D.; Trinder, Debbie; Ganss, Ruth; Leedman, Peter J. (Frontiers in Oncology, 2020)
Iron is an essential nutrient that plays a complex role in cancer biology. Iron metabolism must be tightly controlled within cells. Whilst fundamental to many cellular processes and required for cell survival, excess labile iron is toxic to cells. Increased iron metabolism is associated with malignant transformation, cancer progression, drug resistance and immune evasion. Depleting intracellular iron stores, either with the use of iron chelating agents or mimicking endogenous regulation mechanisms such as microRNAs, present attractive therapeutic opportunities, some of which are currently under clinical investigation. Alternatively, iron overload can result in a form of regulated cell death, ferroptosis, which can be activated in cancer cells presenting an alternative anti-cancer strategy. This review focuses on alterations in iron metabolism that enable cancer cells to meet metabolic demands required during different stages of tumorigenesis in relation to metastasis and immune response. The strength of current evidence is considered, gaps in knowledge are highlighted and controversies relating to the role of iron and therapeutic targeting potential are discussed. The key question we address within this review is whether iron modulation represents a useful approach for treating metastatic disease and whether it could be employed in combination with existing targeted drugs and immune-based therapies to enhance their efficacy.